Morphological and phylogenetic evidence reveal Tetraploa cylindrica sp. nov. (Tetraplosphaeriaceae, Pleosporales) from Saccharum arundinaceum (Poaceae) in Yunnan Province, China - Liao, Chun-Fang; Dong, Wei; Chethana, K. W. Thilini; Pem, Dhandevi; Phookamsak, Rungtiwa; Suwannarach, Nakarin; Doilom, Mingkwan (Phytotaxa, 2022)
During an investigation of fungal saprobes of Yunnan Province, China, a species in Tetraplosphaeriaceae was collected from decaying stems of Saccharum arundinaceum (Poaceae). The taxon has oblong, dark brown to black, four-columned conidia with mostly three long apical appendages. Phylogenetic analyses of combined LSU, SSU, ITS, β-tubulin and tef1-α sequence data revealed that our collection is a member of Tetraploa and has a close affinity to T. aquatica, T. dashaoensis, and T. nagasakiensis. Based on the morphological comparison and multi-locus phylogeny, we introduce T. cylindrica as a new species. The newly discovered taxon is described, illustrated, and compared to related taxa. A taxonomic insight is presented based on our new data regarding the classification problems of asexual and sexual morphs of Tetraploa. In addition, this is the first report of Tetraploa species that occur on Saccharum arundinaceum. The results of the present study will expand our ecological knowledge of Tetraploa.